2021
DOI: 10.1177/1359105321999701
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of perceived effectiveness of preventive behaviors against COVID-19 between the public and medical experts: Not so different in means, but in distributions

Abstract: This brief report documents the results of a survey that measured the public’s and doctors’ perceived effectiveness of preventive behaviors against COVID-19, in Japan. Medical doctors ( n = 117) and the general public ( n = 1086) participated in our online survey. The results of the analysis of mean scores indicate that there were only slight differences in perceived effectiveness between the two groups, while the differences in distributions were remarkable. The results of Silverman’s test suggest the unimoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…[55] A similar result was observed in a study regarding the perceived effectiveness of preventive behaviors against COVID-19. [56] Furthermore, a previous study showed that the intention to wear a mask as a COVID-19 preventive measure was also associated with the perceived norm. [50] The relationship of psychological characteristics with COVID-19 vaccination intention was basically similar among the stratified four Groups, although their statistical significances were slight difference between them.…”
Section: Discussionmentioning
confidence: 99%
“…[55] A similar result was observed in a study regarding the perceived effectiveness of preventive behaviors against COVID-19. [56] Furthermore, a previous study showed that the intention to wear a mask as a COVID-19 preventive measure was also associated with the perceived norm. [50] The relationship of psychological characteristics with COVID-19 vaccination intention was basically similar among the stratified four Groups, although their statistical significances were slight difference between them.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prior studies have confirmed that risk, whether physical, psychological, or financial, has a negative impact on travel or revisit intention (An et al 2010 ; Nik Hashim et al 2019 ). Although recent studies have begun to focus on the perceived effectiveness of protective measures, most of these studies simply focus on comparing the effectiveness of different measures and none have yet studied their impact on travel intention (Nakayachi et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Protective measures, such as sanitization and social distancing, significantly changed how people act during the pandemic. For example, Margraf et al ( 2021 ) and Nakayachi et al ( 2021 ) found that the perceived effectiveness of COVID-19 protective measures differs significantly between countries and between the public and medical experts. However, simply comparing the differences between perceived effectiveness is insufficient in explaining how these differences affect individual behavior during and after the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…We used the available data sets of a study by Nakayachi et al (2021), in which 1,086 Japanese adults evaluated the effectiveness of preventive behaviors designed to curb the spread of COVID-19. The results reported in the present article did not appear in the previous research.…”
Section: Methodsmentioning
confidence: 99%